The Intergenerational Transmission of Gender Role Attitudes: Evidence from Immigrant Mothers-In-Law - Julia Bredtmann; Lisa Sofie Höckel; Sebastian Otten (Institute of Labor Economics (IZA), 2020)
Previous literature has shown that attitudes and preferences are intergenerationally transmitted from parents to their children. We contribute to this literature by analyzing whether gender role attitudes are also transmitted across cultural boundaries, i.e., from immigrants to natives. Focusing on mixed couples, we examine whether the gender role attitudes of foreign-born mothers-in-law can explain the fertility and labor supply decisions of native US women. Our results reveal that women's labor market participation is significantly positively related to the gender role attitudes in her mother-in-law's country of origin. Employing a new identification strategy, we show that this finding is due to the intergenerational transmission of gender norms rather than other unobservable characteristics of the mother-in-law's country of origin. These results suggest that the cultural values held in their source country do not only influence the behavior of immigrants and their descendants, but can also affect the labor force participation of native women. We do, however, not find evidence that intergenerationally transmitted gender role attitudes affect the fertility behavior of native women.
Keywords: J13; J15; J22; D1; 330; intergenerational transmission; gender role attitudes; culture; immigration; fertility; female labor force participation